Last Glacial Maximum Reconstructions of Rwenzori Mountain Glaciers. Issue 1 (20th January 2023) - Doughty, Alice M.; Kelly, Meredith A.; Russell, James M.; Jackson, Margaret S.; Anderson, Brian M.; Chipman, Jonathan; Nakileza, Bob R.
Abstract: The magnitude of tropical cooling during the Last Glacial Maximum (LGM; ∼19–26.5 ka) remains controversial, with sea‐surface temperatures cooling by several degrees less than most temperatures reconstructed at high elevations. To explain this discrepancy, past studies proposed a steeper (increased) lapse rate—the temperature decrease with elevation—during the LGM relative to today. For instance, LGM temperatures in East Africa reconstructed from branched GDGTs from multiple elevations support an ∼0.9°C/km increase in the lapse rate during the LGM relative to present day. Lapse rates are a critical part of the Earth's climate sensitivity and atmospheric energy transfer, and it is vital to know whether and by how much the tropical lapse rate steepened during the LGM. Here, we simulate LGM glacier extents in the Rwenzori Mountains of Uganda with and without a change in lapse rate using a range of temperature and precipitation estimates. We find that the lapse rate must have been steeper than present for glaciers to reach their LGM positions using available sea‐level temperature and precipitation estimates for East Africa. Plain Language Summary: Glaciers are sensitive to changes in temperature and precipitation, and during the last ice age (∼20, 000 years ago), glaciers in the tropics grew in cold (5°C–9°C) and dry conditions while sea surface temperatures changed relatively little (∼1°C–3°C). Perhaps the temperature estimates are telling different stories, or perhaps they are both correct and the rate of cooling with elevation (lapse rate) was steeper (increased) during the drier conditions of the ice age. Here, we use a glacier model and a range of temperature, precipitation, and lapse rate estimates to grow glaciers to moraines (glacial deposits) that mark their ice age extent at 20, 000 years ago. Results indicate that glaciers can reach the moraines using the modest sea surface temperature change and a steeper lapse rate, which is supported by available biogeochemical analysis in this area or a large change in temperature and no lapse rate change, which is not supported by sea surface temperature estimates. Climate alterations in the tropics have global implications, and understanding how the lapse rate can change with time and location is vital for informing climate change models. Key Points: Tropical glaciers in East Africa required significant cooling (5.4°C–7.3°C) to reach their Last Glacial Maximum (LGM) extents A large magnitude of cooling in Afro‐alpine regions conflicts with Indian Ocean sea surface temperatures (1°C–3°C) A steeper (increased) lapse rate during the LGM could explain this altitudinal discrepancy